Kampanye Penggunaan Obat Diabetes dan Obat Lain Selama Puasa - Elsa Maulidina Rahmah; Putri Alissa Setiawan; Nur Annisa Meilina; Linda Astuti; Ahmad Fajri; Faturakhim Faturakhim; Erwin Fakhrani; Fajar Firdaus; Nadya Agustina; Samsul Hadi; Deni Setiawan (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2023)
Adjusting the time of taking medication during fasting is important because it is closely related to drug levels in the blood and its stability in the effective therapeutic range. The level of knowledge on drug use is still very low, both at the hospital, health center and pharmacy levels. Increasing knowledge related to diabetes treatment and drug use in general is very important because of changes in the way people take medicine. The health promotion method is carried out by giving lectures with the help of leaflets. Activities carried out in different health facilities, namely pharmacies, health centers and hospitals. Respondents who took part in this activity were 97 people with an average pretest score of 53.75 and a posttest score of 90. The activity went well and succeeded in increasing the respondents' knowledge of using drugs during fasting.